Mechanisms of impulsive choice: I. Individual differences in interval timing and reward processing - Marshall, Andrew T.; Smith, Aaron P.; Kirkpatrick, Kimberly (My University, 2015)
Impulsive choice behavior incorporates the psychological mechanisms involved in the processing of the anticipated magnitude and delay until reward. The goal of the present experiment was to determine whether individual differences in such processes related to individual differences in impulsive choice behavior. Two groups of rats (Delay Group and Magnitude Group) were initially exposed to an impulsive choice task with choices between smaller-sooner (SS) and larger-later (LL) rewards. The Delay Group was subsequently exposed to a temporal discrimination task followed by a progressive interval task, whereas the Magnitude Group was exposed to a reward magnitude sensitivity task followed by a progressive ratio task. Inter-task correlations revealed that the rats in the Delay Group that made more self-controlled (LL) choices also displayed lower standard deviations in the temporal bisection task and greater delay tolerance in the progressive interval task. Impulsive choice behavior in the Magnitude Group did not display any substantial correlations with the reward magnitude sensitivity and progressive ratio tasks. The results indicate the importance of core timing processes in impulsive choice behavior, and encourage further research examining the effects of changes in core timing processes on impulsive choice.
Keywords: Impulsive behavior; Discounting; Timing; Reinforcer magnitude; Rats